Unusual mode of presentation of intrathoracic bronchogenic cyst: A double location - Fouad Atoini; Aziz Ouarssani; Yassine Ouadnouni; Mohammed Smahi (Respiratory Medicine Case Reports, 2016)
A 63 year old woman presenting chronic back pain and neuralgia had abnormal shadow on chest radiograph. She has a history of pulmonary tuberculosis treated in 1977. The chest-CT scan showed a soft tissue mass in the lower lobe of the right lung and a cystic mass in the paravertebral region. The patient had right lower lobectomy and complete excision of a paraoesophageal cyst. Both masses were bronchogenic cysts at histology. The patient had an uneventful discharge the seventh postoperative day. After 4 years and 7 months of follow-up with CT-scann, the patient was free of symptoms with no evidence of recurrent disease.